Determinasi Kompensasi, Motivasi dan Sistem Karir terhadap Kinerja Karyawan - Romagia SE.,M.Si (STIA Indragiri, 2017)
ABSTRACKCompensation in the enterprise is a very important role in managing human resources in order to provide results or performance is optimal in achieving the targets to be achieved by the company, as well as providing motivation and system, the right career to be able to improve the performance of employees so as to make the achievement of the target company Well done. This study aims to determine the compensation for partial determination of the performance, to find the motivation partially on performance, to determine the career system partially on performance, and determine compensation, motivation and career systems simultaneously on performance. The data used are primary data and secondary data. Primary data was collected using a questionnaire. Secondary data was collected from the documentation such as company profile. The samples in this research using random sampling techniques. The sample size was calculated using the formula slovin. Hypothesis testing is done by t-test for the partial test and F test to test simultaneously. Based on the results of hypothesis testing showed that partial compensation is determined significantly to the performance, the motivation is determined significantly to the performance and the career system is determined significantly on employee performance. Simultaneously, compensation, motivation and career systems is determined significantly on employee performance.